Step-by-step explanation:
The x-intercepts are x = -1 and x = 5, so:
y = k (x + 1) (x − 5)
The vertex is (2, -3), so:
-3 = k (2 + 1) (2 − 5)
-3 = -9k
k = 1/3
y = 1/3 (x + 1) (x − 5)
Simplifying:
y = 1/3 (x² − 4x − 5)
y = 1/3 x² − 4/3 x − 5/3
Answer:
<h2>M(-a, b)</h2>
Step-by-step explanation:
Use the formula of a midpoint:
![\left(\dfrac{x_1+x_2}{2},\ \dfrac{y_1+y_2}{2}\right)](https://tex.z-dn.net/?f=%5Cleft%28%5Cdfrac%7Bx_1%2Bx_2%7D%7B2%7D%2C%5C%20%5Cdfrac%7By_1%2By_2%7D%7B2%7D%5Cright%29)
We have the points P(-2a, 0) and Q(0, 2b). Substitute:
![x=\dfrac{-2a+0}{2}=\dfrac{-2a}{2}=-a\\\\y=\dfrac{0+2b}{2}=\dfrac{2b}{2}=b](https://tex.z-dn.net/?f=x%3D%5Cdfrac%7B-2a%2B0%7D%7B2%7D%3D%5Cdfrac%7B-2a%7D%7B2%7D%3D-a%5C%5C%5C%5Cy%3D%5Cdfrac%7B0%2B2b%7D%7B2%7D%3D%5Cdfrac%7B2b%7D%7B2%7D%3Db)
Ex.
f + g = y
-----------
3
3(f+g) = (y) 3
--------
3
f + g =3y
f - f + g = 3y - f
g = y - f
Answer:
Step-by-step explanation:
(14 + 7)/2 = 21/2= 10.5
(-2 + (-8))/2= -10/2= -5
Midpoint(10.5, -5)
-2 is a degree 0 polynomial with 1 term and 0 variables